How surprising! Epistemic emotions and perceived credibility mediate the relation between prior beliefs and responses to fake and true news - Waldzus, S.; Rijo, A. (General Meeting of the European Association of Social Psychology (EASP), 2023)
Whether and when people are deceived by fake news often depends on their prior beliefs on the topic at stake. Research guided by cognitive theories has produced ambiguous results with regard to whether fake news detection is undermined by lack of systematic reasoning (classical approach) or also by effortful but wishful thinking (motivated reasoning). Integrating ideas from the two approaches, a Bayesian approach to fake news reception has been proposed, assuming that posterior beliefs on news issue are versions of prior beliefs that are updated based on new incoming information, with the updating process itself being influenced by the prior belief. To test whether epistemic emotional responses (interest, surprise) and perceived credibility mediate the relation between prior belief and news reception, we presented preselected true and false news posts referring to dysfunctional aspects of the system (e.g., corruption cases) to 259 participants in an online study. As predicted, epistemic emotions and perceived credibility mediated the relation between prior beliefs in the democratic system and accuracy ratings as well as sharing intentions. There was an unpredicted link between epistemic emotions and perceived credibility, suggesting sequential (prior belief, emotions, credibility, accuracy attribution + sharing) rather than parallel mediation. We conclude that reception of fake and true news depends on emotionally biased credibility cues, influenced by prior beliefs.